Model of the Emotionally-Valuable Component of the Content of Foreign Language Education in Middle School - Nickolaevna Tatarinova, Maya; Stanislavovna Kuklina, Svetlana; Anatolyevna Cheremisinova, Rimma; Igorevna Shevchenko, Anna; Valeryevna Shcherbakova, Tatyana; ., . (International Journal of Engineering and Technology, 2018)
The purpose of this article is to present an invariant of the basic model of the emotionally-valuable component (EVC) of the content of school foreign language (FL) education for its second stage (forms 5-7). Methods of theoretical analysis (systemic-structural, organizational, functional, comparative, typological) as well as designing and modelling were used. The basic model of the EVC of the content of school FL education is presented. Then it is adapted to the conditions of teaching FL at the middle stage of a comprehensive school. It allows to implement the EVC of the content of FL education at this stage and make another step in a pupilâ€™s formation as a multicultural linguistic personality.Â Â